2017
DOI: 10.1080/10717544.2016.1245368
|View full text |Cite
|
Sign up to set email alerts
|

Passive targeting and lung tolerability of enoxaparin microspheres for a sustained antithrombotic activity in rats

Abstract: Pulmonary bed can retain microparticles (MP) larger than their capillaries' diameter, hence we offer a promising way for lung passive targeting following intravenous (IV) administration. In this study, enoxaparin (Enox)-albumin microspheres (Enox-Alb MS) were, optimally, developed as lung targeted sustained release MP for IV use. Lung tolerability and targeting efficiency of Enox-Alb MS were tested, and the pharmacokinetic profile following IV administration to albino rats was constructed. In vivo studies conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…amine and thiol) could be incorporated into the surface layer of polydopamine (PDA) via Michal addition or Schiff base reactions (Lee et al., 2009 ; Park et al., 2014 ). For these reasons, we selected an amine-terminated PEG-FA copolymer as the targeting ligand incorporated into PDA coated CA-PLGA/NPs to ensure efficient passive accumulation (Ibrahim et al., 2017 ) and simple universal active targeting.…”
Section: Introductionmentioning
confidence: 99%
“…amine and thiol) could be incorporated into the surface layer of polydopamine (PDA) via Michal addition or Schiff base reactions (Lee et al., 2009 ; Park et al., 2014 ). For these reasons, we selected an amine-terminated PEG-FA copolymer as the targeting ligand incorporated into PDA coated CA-PLGA/NPs to ensure efficient passive accumulation (Ibrahim et al., 2017 ) and simple universal active targeting.…”
Section: Introductionmentioning
confidence: 99%
“…In the sections of this group, the alveolar wall was damaged, and alveolar epithelial cells were disorganized; leucocytes, cell shed debris, and apoptotic cells were present in many alveoli. In the study of Ibrahim et al 27 , lungs showed normal histological structures of the bronchioles, air alveoli, and blood vessels in both groups with no histopathological alterations after injection of control and Enoxaparin. They have not observed emboli or tissue infarction, macro-or microscopically in any of the samples.…”
Section: Discussionmentioning
confidence: 85%
“…Later, the formula below permitted the calculation of these nanoencapsulated substances. 14,15 EE(%) = − × Total initial drug Drug in supernatant Total initial drug 10 00…”
Section: Determination Of Entrapment Efficiency (Ee)mentioning
confidence: 99%